2014
DOI: 10.1089/neu.2013.3110
|View full text |Cite|
|
Sign up to set email alerts
|

Traumatic Brain Injury-Induced Ependymal Ciliary Loss Decreases Cerebral Spinal Fluid Flow

Abstract: Traumatic brain injury (TBI) afflicts up to 2 million people annually in the United States and is the primary cause of death and disability in young adults and children. Previous TBI studies have focused predominantly on the morphological, biochemical, and functional alterations of gray matter structures, such as the hippocampus. However, little attention has been given to the brain ventricular system, despite the fact that altered ventricular function is known to occur in brain pathologies. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 59 publications
(83 reference statements)
5
43
0
Order By: Relevance
“…In a previous study 16 and the present report, we showed that methanol treatment is necessary for immunofluorescent and immunogold staining of ependymal basal bodies in paraformaldehyde-fixed brain slices. With the present optimization, treatment with methanol at the concentration from 33.3% to 75% can result in ideal staining of basal bodies without inducing obvious deformations to the brain slices.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In a previous study 16 and the present report, we showed that methanol treatment is necessary for immunofluorescent and immunogold staining of ependymal basal bodies in paraformaldehyde-fixed brain slices. With the present optimization, treatment with methanol at the concentration from 33.3% to 75% can result in ideal staining of basal bodies without inducing obvious deformations to the brain slices.…”
Section: Discussionsupporting
confidence: 62%
“…The rabbit polyclonal antibody against γ-tubulin was used to stain out the basal bodies of ependymal cells, as shown previously. 16 Before immunostaining, we applied different concentration of methanol to regular vibratome slices at RT for 30 minutes or to sucrose-protected slices at −20°C for 10 minutes. From the concentration of 33.3% to 100%, methanol treatment at both temperature conditions resulted in a similar immunofluorescent staining pattern of basal bodies in these brain slices (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Intravital particle tracking has been used to indirectly observe blood flow velocity with tracer particles in the systemic circulation [107-110] and in the colonic microcirculation in experimental inflammatory bowel disease (IBD) [111], as well as to indirectly observe decreases in cerebrospinal fluid flow after traumatic brain injury [112]. More recently, intravital particle tracking techniques have been adapted to tracking NP for drug and gene delivery in vivo in real time.…”
Section: The Utility Of Particle Tracking Analysis In Drug and Genmentioning
confidence: 99%
“…Ependymal cells are specialized glia, that line the ventricles of the CNS. Ependymal cell lose was found to decrease ventricular flow following TBI which could negatively affect the waste and nutrient exchange within the brain (Xiong et al, 2014 ). Additional research that helps decipher the molecular pathways between glia and memory deficits will be vital for development of better clinical tools for gauging memory loss.…”
Section: Glial Contribution To Memory Deficitsmentioning
confidence: 99%